Anti-colonial feminism: discourses of Gayatri Chakravorty Spivak and Ania Loomba - Hasan, Md. Mahmudul (Asiatic Society of Bangladesh, 2004)
Feminist movements in the present day bring revolutionary ideas to many established notions, social mythologies and, most importantly, the literary canon. With the development of various kinds of thinking within feminism, it incorporates a range of perspectives: Western feminism, post-colonial feminism, Oriental feminism, anti-colonial feminism, Black feminism, capitalist or corporate feminism, Marxist feminism, international feminism, so on and so forth. Feminist theorists and philosophers are contributing to these trends from their own critical position that, in most cases, reflects, among other things, the background from which they come and their own experiences within feminist theoretical framework. Similarly, feminist literary criticisms are shaking the very foundation of the established trends of literary criticisms. But, ironically enough, feminist literary criticism itself has come under serious scrutiny and re-examination because of its alleged lack of concern for the experiences of the non-Western feminist heroines and to the feminist literary heritage of subaltern societies. Although, since its inception feminist literary criticism has gone much further in ideological and theoretical terms, it cannot come out of the indictment of parochialism and insularity yet; because subaltern feminist experiences have not found an equal standing in global feminist arena. An equal representation of women from different ethnic, religious and geographical backgrounds, which would give feminisms credits of credibility in terms of global sisterhood, is still nonexistent in the established [Western] feminist thinking.